Relationship between autonomic dysfunction and sexual dysfunctions in Parkinson’s patients - Varlıbaş, Hatice; Erdoğan, Hacı Ali; Acir, Ibrahim; Yayla, Vildan (Frontiers in Aging Neuroscience, 2025)
ObjectiveParkinson’s disease (PD) is a neurodegenerative disorder characterized by motor and non-motor symptoms. Autonomic dysfunction, one of the non-motor symptoms, affects various systems such as the gastrointestinal, cardiovascular, genitourinary, and thermoregulatory systems. Sexual dysfunction (SD), however, is a frequently neglected issue in Parkinson’s patients. This study aimed to investigate the relationship between SD, findings of autonomic dysfunction in other systems, and the severity of PD.MethodsThe study included 41 male and 35 female patients diagnosed with definitive idiopathic PD, with Hoehn and Yahr stages between 1 and 3, and without a diagnosis of diabetes or cognitive impairment. Demographic characteristics and disease duration of the patients were recorded. The following assessments were administered to the patients: Unified Parkinson’s Disease Rating Scale (UPDRS), Hoehn and Yahr Scale, Beck Depression Inventory (BDI), SCOPA-AUT questionnaire (Scales for Outcomes in Parkinson’s Disease Autonomic Dysfunction), short version of the QUIP (Questionnaire for Impulsive-Compulsive Disorders in Parkinson’s Disease), and ASEX (Arizona Sexual Experiences Scale).ResultsThe patients were divided into two groups: those with SD (53.9%) and those without SD (46.1%). Patients with SD had significantly higher age, PD stage, total SCOPA-AUT scores, and subdomain scores related to the cardiovascular, urinary, and gastrointestinal systems compared to those without SD (p < 0.001). The prevalence of hypertension was also significantly higher in the SD group (p = 0.001). An increase in UPDRS scores and depression severity, as measured by the Beck Depression Inventory, was associated with higher ASEX scores (p < 0.001). The frequency of impulse control disorder (ICD) was 6.5%; no significant differences were observed between patients with and without ICD in terms of equivalent levodopa dose or age (p = 0.58, p = 0.76).ConclusionAlthough the presence of sexual dysfunction in Parkinson’s disease and its negative impact on quality of life have been recognized for many years, it is often overlooked for various reasons. The significant relationship identified in our study between SD, the severity of autonomic dysfunction, and disease stage may raise awareness of the early recognition of SD in PD patients. This could help prevent the neglect of this important non-motor symptom in disease management.